Nitrogen doping of metallic single-walled carbon nanotubes:n-type conduction and dipole scattering - KRSTIC, VOJISLAV (IOP Publishing, 2007)
The charge transport properties of individual, metallic nitrogen doped, single-walled carbon nanotubes are investigated. It is demonstrated that n-type conduction can be achieved by nitrogen doping. Evidence was obtained by appealing to electric-field effect measurements at ambient condition. n-type conduction is attributed to the presence of graphite-type nitrogen. The observed temperature dependencies of the zero-bias conductance indicate a disordered electron system with electric-dipole scattering, caused mainly by pyridine-type nitrogen atoms in the honeycomb lattice.
PUBLISHED
Keywords: Physics